Sculpture in the Age of Doubt. - McEvilley, Thomas (New York : Allworth Press, 1999)
Duchamp, Marcel ; Broodthaers, Marcel ; Oppenheim, Dennis ; Kounellis, Jannis ; Samaras, Lucas ; Orr, Eric ; Laib, Wolfgang ; Abramovic, Marina ; Tracy, Michael ; Gormley, Antony ; Kapoor, Anish ; Boezem, Marinus ; Bourgeois, Louise ; Chin, Mel ; Byars, James Lee ; Oppenheim, Meret ; Kienholz, Edward ; Sterbak, Jana ; Cragg, Tony (Anthony) ; Torres, Francesc ; Reichek, Elaine ; Drew, Leonardo ; Merz, Gerhard ; Bradshaw, Dove ; Croak, James
Engels
boek